2005
DOI: 10.1007/s10661-005-2382-1
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals in Liver and Muscle of Bluefin Tuna (Thunnus thynnus) Caught in the Straits of Messina (Sicily, Italy)

Abstract: The present investigation was carried out on the bluefin tuna (Thunnus thynnus) collected during the month of April 2003 from the Straits of Messina. The aim of this study is to determine heavy metal levels (Cd, Cu, Hg, Mn, Pb and Zn) in liver and muscle tissues of 14 Thunnus thynnus of different age and sex and to investigate the relationships between fish sex and size (length and weight) and metal concentrations in the tissues. The concentrations of the various metals were determined by a Varian atomic absor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
3
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(57 citation statements)
references
References 26 publications
(28 reference statements)
6
45
3
3
Order By: Relevance
“…In this study, the accumulation of the some elements in diff erent parts of both wild and farmed the BFT was evaluated. The levels obtained were similar to those found by other authors 2,9,[11][12][13][14]18 .…”
Section: Discussionsupporting
confidence: 91%
“…In this study, the accumulation of the some elements in diff erent parts of both wild and farmed the BFT was evaluated. The levels obtained were similar to those found by other authors 2,9,[11][12][13][14]18 .…”
Section: Discussionsupporting
confidence: 91%
“…Yet, dominating Hg levels in muscle, as it was noted for Common Dolfinfish of the Mozambique Channel, have also been observed in Bluefin Tunas fished in the Messina straits (Licata et al, 2005), and in benthic fish caught around the Kerguelen Islands (Bustamante et al, 2003). Moreover, elemental turnover rates are, as a general rule, higher in liver and kidney than in muscle.…”
Section: Elemental Distribution Among Tissuesmentioning
confidence: 53%
“…Mackay et al, 1975;Jaffar and Ashraf, 1988;Canli and Atli, 2003;Bustamante et al, 2003;Storelli et al, 2005;Licata et al, 2005). Interestingly the accumulation pattern of Cd in fish differs from that of other vertebrates such as birds, mammals and turtles in which kidney is the target tissue for Cd (e.g.…”
Section: Elemental Distribution Among Tissuesmentioning
confidence: 99%
“…Figure 2 showed that partitioning among tissues varied with the studied elements. Mackay et al, 1975;Canli and Atli, 2003;Deheyn et al, 2005;Licata et al, 2005). The organotropism is most likely related to tissue function and element affinity to certain proteins such as metallothioneins (MTs), besides the availability of elements in water and food (Hamilton and Mehrle, 1986;Roesijadi, 1992;De Smet et al, 2001;Atli and Canli, 2003).…”
Section: Resultsmentioning
confidence: 99%